2014
DOI: 10.1159/000369344
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Background Incidence Rates of Guillain-Barré Syndrome in Germany - A Retrospective Cohort Study with Electronic Healthcare Data

Abstract: Background: The Guillain-Barré syndrome (GBS) occurs after infections and as an adverse reaction to vaccines. No detailed information on incidence rates (IRs) in Germany is available. Methods: This retrospective cohort study estimated age- and sex-specific IRs of GBS in Germany in the years 2007-2009 based on electronic healthcare data from the German Pharmacoepidemiological Research Database (GePaRD). Two case definitions were applied. GBS cases had a main discharge diagnosis of GBS. GBS_PROCEDURE cases in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
14
16
0
Order By: Relevance
“…Patterns of IR with respect to age and sex distributions in adults were similar to those observed in other populations (Sejvar et al , ; Shui et al , ; Hense et al , ; Benedetti et al , ; Huang et al , ) . In particular, in a German study based on 889 GBS cases, a more marked increase in the incidence of GBS was observed after the age of 50 which reached a peak between the ages of 70 and 79 (Hense et al , ) . Several studies have reported a decrease in GBS incidence after the age of 80 (Cheng et al , ; Chen et al , ; Hense et al , ; Peric et al , ; Benedetti et al , ; Rivera‐Lillo et al , ) .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Patterns of IR with respect to age and sex distributions in adults were similar to those observed in other populations (Sejvar et al , ; Shui et al , ; Hense et al , ; Benedetti et al , ; Huang et al , ) . In particular, in a German study based on 889 GBS cases, a more marked increase in the incidence of GBS was observed after the age of 50 which reached a peak between the ages of 70 and 79 (Hense et al , ) . Several studies have reported a decrease in GBS incidence after the age of 80 (Cheng et al , ; Chen et al , ; Hense et al , ; Peric et al , ; Benedetti et al , ; Rivera‐Lillo et al , ) .…”
Section: Discussionsupporting
confidence: 85%
“…The IR observed in this study, based on principal discharge diagnosis, is situated in the upper range of previous estimates of GBS incidence in Europe and North America (McGrogan et al , ; Sejvar et al , ; Shui et al , ; Hense et al , ; Benedetti et al , ) . In children, the IR was slightly higher than the estimate of 0.6 reported by Sejvar et al ( ) , but lower than those reported in developing countries (McGrogan et al , ; Islam et al , ; Rivera‐Lillo et al , ) .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Interestingly, it seems that in Europe the incidence of GBS decreases from North (Sweden, UK, and Germany) to South (Spain, Italy, Western Balkans, and Greece) (Congia et al, ; Cheng et al, ; Cuadrado et al, ; Chroni et al, ; Hughes et al, ; Hense et al, ; Peric et al, ) . We found the opposite case in the southern hemisphere with an increase from the north of Chile (North and Far North) to the south (South and Far South).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal predominance, a distinctive feature in some geographic areas, has been discussed [6][7][8][9][10] . Influenza virus and vaccines have also been suspected to be stimuli for development of GBS [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%